2011
DOI: 10.1007/s11095-011-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Organic Glasses: Effects of Polymer Additives on Bulk and Surface Crystal Growth in Amorphous Nifedipine

Abstract: Polymer additives inhibit crystal growth in nifedipine glasses more strongly in the bulk than at the surface. The effectiveness of crystallization inhibitors depends not only on intermolecular interactions but also on molecular sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
120
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 46 publications
(56 reference statements)
9
120
1
Order By: Relevance
“…This inhibitory effect is remarkable and suggests that lowconcentration polymer additives can substantially stabilize amorphous drugs against crystallization. Their finding was substantiated by Cai et al (69), who showed that the logarithm of the bulk crystal growth rate decreases linearly with the concentration of PVP in weight percent (Fig. 7).…”
Section: Polymer Additives Can Have Different Effects On Bulk and Surmentioning
confidence: 59%
See 4 more Smart Citations
“…This inhibitory effect is remarkable and suggests that lowconcentration polymer additives can substantially stabilize amorphous drugs against crystallization. Their finding was substantiated by Cai et al (69), who showed that the logarithm of the bulk crystal growth rate decreases linearly with the concentration of PVP in weight percent (Fig. 7).…”
Section: Polymer Additives Can Have Different Effects On Bulk and Surmentioning
confidence: 59%
“…Although PVP additives can strongly inhibit bulk crystal growth in NIF glasses, their effect on surface crystal growth is much weaker (69). Figure 7 shows that both log u s and log u b decrease linearly with increasing concentration of PVP K15 in weight percent, log u b decreases approximately three times faster than log u s .…”
Section: Polymer Additives Can Have Different Effects On Bulk and Surmentioning
confidence: 99%
See 3 more Smart Citations